TAFSIR DAKWAH DALAM KIDUNG PANGILING - Miftakhur Ridlo (LP2M Universitas Ibrahimy, 2020)
In a broad outline, the interpretation of Da'wah in Kidung Pangiling by Imam Malik includes 4 types. They are about the creed or faith, sharia or worship, morals and culture. The following is a song about faith: “2006 luweh gede tekane bendu Ilang imane syetan ketemu Rusak ikhlase ramene padu Ilmu amale syetan seng digugu”. It has meaning that in 2006 there were greater trials that came, the loss of faith and meeting with shaitan, the loss of sincerity and the fight, the use of demonic science. The next one is a song about sharia: “Syahadat limo sing di ugemi Satriyo piningit yo imam Mahdi Ngetrapno hukum lewat kitab kang suci Sing ora pisah dawuhe nabi”. The meaning of that song is the five creeds is held, Satria Piningit O Imam Mahdi, carrying out the law through the scripture, which will not be separated from the words of the Prophet. Furthermore a song about morals: “Mulo sedulur kudu seng akeh syukure Marang wong kuno tumprap bahasane Anane pepeling sing supoyo ati – ati uripe Cak biso selamet ndunyo akhirate”. It has meaning that you have to be thankful, speak delicately with parents, reminders to be careful, become able to survive the afterlife. The last is a song about culture: “Negoro Ngastino wis kompak banget Nyusun kekuatan supoyo menang lan selamet Negoro Ngamarto supoyo ajur lan memet Ngedu pendowo sampek dadi gemet”. That meaning is Ngastino have jointly arranged forces to win and survive. So that Ngamarto was completely destroyed and pandawa complained to become cowards.